2018
DOI: 10.1016/j.ejphar.2018.08.008
|View full text |Cite
|
Sign up to set email alerts
|

Neuropharmacology of attention

Abstract: Early philosophers and psychologists defined and began to describe attention. Beginning in the 1950's, numerous models of attention were developed. This corresponded with an increased understanding of pharmacological approaches to manipulate neurotransmitter systems. The present review focuses on the knowledge that has been gained about these neurotransmitter systems with respect to attentional processing, with emphasis on the functions mediated within the medial prefrontal cortex. Additionally, the use of pha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 107 publications
0
13
0
Order By: Relevance
“…For example, the animals may keep track of the elapse of time more precisely under the random-delay condition in an effort to predict future delay durations based on the past ones. Different levels of neuromodulatory signals associated with different levels of attention (i.e., higher attention during the random-delay condition) 29 may underlie the observed differences in mPFC neural activity between the fixed and random delay conditions, which remains to be studied.…”
Section: Discussionmentioning
confidence: 99%
“…For example, the animals may keep track of the elapse of time more precisely under the random-delay condition in an effort to predict future delay durations based on the past ones. Different levels of neuromodulatory signals associated with different levels of attention (i.e., higher attention during the random-delay condition) 29 may underlie the observed differences in mPFC neural activity between the fixed and random delay conditions, which remains to be studied.…”
Section: Discussionmentioning
confidence: 99%
“…Previous research has indicated that the onset of memory decline may vary among different memory types, with episodic memory decline possibly being lifelong. 23 Our study could not explore the onset age of memory decline without performing regression among different age groups. The significant coefficient may indicate memory decline associated with SHS exposure.…”
Section: Discussionmentioning
confidence: 98%
“…The basal forebrain (BF) is a brain region which degenerates in dementia [5][6][7] and is implicated in the negative effects of sleep disruption on vigilance and cognition 8,9 . Previous studies demonstrated that the BF controls cortical fast oscillations that underlie attention [10][11][12] and revealed the important role of cholinergic neurons [13][14][15] . However, the role of other neurochemically defined BF subtypes is unknown.…”
Section: Discussionmentioning
confidence: 99%